Continuous Choreographies as Limiting Solutions of N-body Type Problems with Weak Interaction - Castaneira, R.; Padilla, P.; Sánchez-Morgado, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We consider the limit N→+∞ of N-body type problems with weak interaction, equal masses and −σ-homogeneous potential, 0<σ<1. We obtain the integro-differential equation that the motions must satisfy, with limit choreographic solutions corresponding to travelling waves of this equation. Such equation is the Euler-Lagrange equation of a corresponding limiting action functional. Our main result is that the circle is the absolute minimizer of the action functional among zero mean (travelling wave) loops of class H¹.